MEMAHAMI PROSES PENGREKRUTAN DAN SELEKSI, JENJANG KARIR DAN PANGKAT DALAM KEPOLISIAN - Artika Cesar Aura Devi; Chyntia Martini, Nadia Karin, Zahra Permata Sari, Tugimin Supriyadi (CV. Adiba Aisha Amira, 2024)
The National Police of the Republic of Indonesia (Polri) is an institution that plays a crucial role in maintaining public security and order. The recruitment and selection process in the police force is a very critical initial stage to ensure that only qualified candidates are accepted. The recruitment process includes announcements, registration, administrative selection, physical selection, written tests, psychological tests, interviews, and medical examinations. Psychological tests are important to assess the emotional stability and character of the candidates. The